THE INFLUENCE OF PROMOTION AND BRAND IMAGE ON THE PURCHASE DECISION OF PT DUTA INTIGUNA YASA (MR. DIY) CENTRAL TAPANULI REGENCY - Raflisyach Dandung Panggabean (Patua : Journal of Business Administration and Management, 2025)
The purpose of this study is to find out and analyze whether promotion and brand image of purchase decisions can facilitate employee duties in serving consumers of PT Duta Intiguna Yasa (MR. DIY) Central Tapanuli Regency. The type of research used in this study is the survey method, which is a method used to obtain data from certain natural places and research collects data through observation, dissemination of questionnaire documentation and interviews. The data analysis technique in this study is Multiple Linear Regression. Based on the autocorrelation test, the three variables, namely the promotion variable (X1) and the brand image variable (X2) with the purchase decision variable (Y) is 0.728 which means that there is a positive correlation and is classified as high correlation. Where from the results of regression analysis with the equation Y = 1.731 + 0.509 X1 + 0.429X2. The hypothesis proposed by the author reads the Influence of Promotion and Brand Image on the Purchase Decision of PT Duta Intiguna Yasa (MR. DIY) Central Tapanuli Regency is acceptable because the tcount value is 3.150 > ttable is 2.004 and the significant level value (Sig) is 0.003 < 0.05. It can therefore be concluded that Ho is rejected and Ha is accepted, which means that Promotion (X1) has a significant effect on the Purchase Decision (Y). and tcount of 3.694 < ttable of 2.004 and significant level value (Sig) 0.001> 0.05. Therefore, it can be concluded that Ho is accepted and Ha is rejected, which means that Brand Image (X2) has an insignificant effect on the Purchase Decision (Y). The magnitude of the influence of variables X1 and X2 on variable Y is 0.530 or 74% and the remaining 47% is determined by other factors that are not discussed in this study.